Effect of clitoral massage on levels of estradiol, testosterone, dehydroepiandrosterone sulphate and pregnancy rate in cows - Bozkurt, T; Türk, G; Gür, S (My University, 2007)
This study was conducted to investigate the effect of clitoral massage on levels of estradiol (E2), testosterone (T), dehydroepiandrosterone sulphate (DHEA-S) and pregnancy rate in cows. For this purpose, 38 Holstein cows ranging from 3-6 years old were used. The cows were divided into two groups, as control (n=19) and application (n=19). The degree of intensity of oestrus expression was scored on a scale of 0 to 5 by considering knowledge of anamnesis, findings of rectal palpation and inspection as a criteria. All animals of both groups were artificially inseminated by recto-vaginal method with frozen-thawed bull semen. Clitoral massage was applied to the cows in the application group for 15-30 sec. after artificial insemination. Blood samples were then taken from jugular vein and centrifuged at 5000 rpm for 5 m., and serum samples were stored deep-frozen at -20 oC. Levels of E2, T and DHEA-S were determined by RIA method. All animals were examined by rectal palpation of the uterus for pregnancy on day 75 after insemination. Clitoral massage application had no significant effect on the levels of E2, T, DHEA-S and pregnancy rate in cows. There was a significant difference (P<0.05) in the degree of the intensity of oestrus between control and application groups. A significant negative correlation (P<0.01, r = -0.93) was found between levels of E2 and T.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: clitoral massage estradiol testosterone dehydroepiandrosterone sulphate pregnancy rate cow